Stability and Adaptability Genotype of Hybrid Rice in the West Java Province of Indonesia - Amalia , Lia; Komariah, Ai; Hilmayanti, Ilma (Asian Journal of Agriculture and Rural Development, 2019)
Experiments to study the stability and adaptability genotype of hybrid rice were conducted in two locations in West Java: 1. the Jelekong Village Baleendah Bandung region, 2. the Arjasari Village Leuwisari Tasikmalaya region. The altitude of the Baleendah Bandung region is 650 and that of the Leuwisari Tasikmalaya region is 450 meters above sea level. The experiments were arranged in a randomized block design and used with 9 genotypes and 3 replications. The 9 genotypes of hybrid rice are SW-907, SW-804, SW-902, US-915, SW-82, SW-923, Intani-2, SL 8 SHS, and SHS 04 WM. The result of the experiment showed that the whole genotypes A = SW-907, B = SW-804, C = SW-902, D = US-915, E = SW-82, F = SW- 923, G = WM 4 SHS, H = SL 8 SHS, and I = Intani 2 measured the height of the plants, the number of productive tillers, the length of the panicles, the number of grains per panicle, the number of filled grains per panicle, the weight of 1000 grains, and the grain yield per plot, and were unstable and unadaptive in Bandung and Tasikmalaya.